2021
DOI: 10.1111/mec.15890
|View full text |Cite
|
Sign up to set email alerts
|

Pollinators mediate floral microbial diversity and microbial network under agrochemical disturbance

Abstract: How pollinators mediate microbiome assembly in the anthosphere is a major unresolved question of theoretical and applied importance in the face of anthropogenic disturbance. We addressed this question by linking visitation of diverse pollinator functional groups (bees, wasps, flies, butterflies, beetles, true bugs and other taxa) to the key properties of the floral microbiome (microbial α‐ and β‐diversity and microbial network) under agrochemical disturbance, using a field experiment of bactericide and fungici… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 73 publications
(167 reference statements)
0
44
0
Order By: Relevance
“…It has been reported that insect visitors play important roles in vectoring flower microbes in M . japonicus and many other plant species (Russell et al, 2019; Ushio et al, 2015; Wei et al, 2020), while the importance of dispersal by flower visitors may differ between male and female flowers or among microbes. Insect visitors may be important vectors of some bacteria, such as ASV02P1, ASV03M1, ASV04E1, and ASV09E2 abundant on male flowers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that insect visitors play important roles in vectoring flower microbes in M . japonicus and many other plant species (Russell et al, 2019; Ushio et al, 2015; Wei et al, 2020), while the importance of dispersal by flower visitors may differ between male and female flowers or among microbes. Insect visitors may be important vectors of some bacteria, such as ASV02P1, ASV03M1, ASV04E1, and ASV09E2 abundant on male flowers.…”
Section: Discussionmentioning
confidence: 99%
“…Pollinators and herbivores carry microbes on their body surface, in their gut system, or on the surface of the pollen attached to their body (Herrera et al, 2009; Manirajan et al, 2018; Sasu et al, 2010; Ushio et al, 2015), though their effects may vary among visitor groups and individuals. A recent study (Wei et al, 2020) showed that different pollinator guilds had distinct effects on both the alpha and beta diversity of floral microbes on cultivated strawberries. Bees, which are extensive foragers, increased alpha diversity by enhancing colonization, while true bugs and flies contributed to microbial community differentiation and increased beta diversity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study was conducted in a diverse serpentine seep co‐flowering community at the McLaughlin Natural Reserve in northern California, USA (38°51′41.4″N, 122°23′54.8″W; banana slug site in Koski et al, 2015; Wei et al, 2021). This reserve is part of the University of California Natural Reserve System, which provided permission to conduct the study.…”
Section: Methodsmentioning
confidence: 99%
“…plant communities; Ashman et al, 2020; Götzenberger et al, 2012). This is mainly due to the difficulty of incorporating the intrinsic complexities of species‐rich communities and the interactions within them (Ashman et al, 2020; Götzenberger et al, 2012; Hegland et al, 2009; Wei et al, 2021). This gap in knowledge has in turn hindered our ability to gain a more complete understanding of the ecological processes and underlying mechanisms that shape natural communities (Ashman et al, 2020; Götzenberger et al, 2012; Wolowski et al, 2017).…”
Section: Introductionmentioning
confidence: 99%